Effect of storage time on the ionic conductivity of chitosan-solid polymer electrolytes incorporating cyano-based ionic liquids - Leones, Rita Daniela Barros (2017)
Four solid polymer electrolytes (SPEs) of chitosan-based host matrix were prepared by solvent casting method. The SPEs incorporated 1-ethyl-3-methylimidazolium thiocyanate ([C2mim][SCN]), 1-ethyl-3- methylimidazolium dicyanamide ([C2mim][N(CN)2]), 1-ethyl-3-methylimidazolium tricyanomethanide ([C2mim][C(CN)3]), and 1-butyl-3-methylimidazolium thiocyanate ([C4mim][SCN]). The structure, morphology, thermal behavior, and electrochemical properties of the synthesized free-standing transparent membranes were studied. It was verified that all the samples are amorphous and thermally stable. TGA of chitosan[C2mim][N(CN)2] membrane showed a Tonset of ca. 100 C (232 C) higher than the Tonset of the chitosan matrix (135 C), highlighting the ionic liquids (ILs) stabilizing effect on the polymer host. The highest ionic conductivity was exhibited by chitosan[C2mim][SCN] with 1.61 10–3 S cm-1 at 25 C and 1.28 10–2 S cm-1 at 100 C. Two years later these ionic conductivity values were still very high (>10–4 S cm-1) and adequate for application in solid-state electrochemical devices (ECDs). Such results attest to the samples long shelf-life, proving that these chitosan[Cnmim][X(CN)m] SPEs are time stable, and thus may easily find practical applications.